Climatic variability over the last 30,000 years recorded in La Piscina de Yuriria, a Central Mexican Crater lake - Holmes, Jonathan; Metcalfe, Sarah E.; Jones, Heather L.; Marshall, Jim D. (Wiley, 2016)
The Trans-Mexican Volcanic Belt provides an excellent setting for reconstruction of late Quaternary climate from different natural archives. Moreover human impact on the landscape since the mid Holocene provides a good opportunity to investigate the complex interplay of natural and anthropogenic forcing of landscape change. However despite the wealth of records, understanding of the environmental history of the region and its wider significance for climate change across the northern neotropics remains incomplete. We present a radiocarbon-dated, multiple-proxy (sedimentology, sedimentary geochemistry, ostracods, diatoms, stable isotopes) record of climatic and environmental change based on the lacustrine sediments from La Piscina de Yuriria, a hydrologically-closed volcanic crater in the northern TMVB. Much of the last glacial interval was characterised by low effective moisture associated with a weakened North American Monsoon (NAM) although the interval from 30,000 to 27,500 aBP experienced abrupt changes in rainfall. The period corresponding to the late glacial stadial was also dry and the lake may have dried out at this time. There was a change to wetter but variable conditions during the early Holocene as the NAM strengthened. Progressive drying during the later Holocene was accompanied by phases of catchment disturbance, which were partly the result of human impact.